The Effect of Local Coffee Shop Marketing Mix on Customer Satisfaction and Loyalty in Indonesia - Hasbiah, Sitti (Bulletin of Management and Business, 2025)
This study aims to analyze the influence of marketing mix factors on customer satisfaction and the subsequent relationship between customer satisfaction and customer loyalty in the context of coffee shops in Makassar. As coffee shops face increasing competition, understanding the dynamics between marketing strategies, customer satisfaction, and loyalty becomes crucial for sustaining growth and achieving differentiation in the marketplace. The research employs multiple regression analysis to evaluate the influence of seven marketing mix elements—product, price, location, promotion, process, physical evidence, and people—on customer satisfaction. Additionally, simple regression analysis is used to assess the impact of customer satisfaction on loyalty. Data for this study are collected through structured questionnaires distributed to coffee shop customers in Makassar. The results reveal that among the seven marketing mix factors, the "people" and "process" dimensions exert the most significant influence on customer satisfaction. Sympathetic and engaging employee interactions, combined with efficient and seamless service processes, contribute significantly to enhancing customer experiences. Conversely, factors such as "location" and "physical evidence" are found to have no significant impact on customer satisfaction, suggesting that other elements of the marketing mix may play a more pivotal role in shaping customer perceptions. Furthermore, the findings confirm that customer satisfaction significantly affects customer loyalty. Satisfied customers are more likely to return, recommend the coffee shop to others, and exhibit long-term loyalty. This underscores the importance of delivering a consistent and satisfying experience that aligns with customer expectations. The study provides important managerial implications for local coffee shops seeking to enhance their competitive advantage. Prioritizing service quality, fostering positive interactions between staff and customers, and optimizing service processes can create a differentiated customer experience. By focusing on these aspects, coffee shops can cultivate higher levels of customer satisfaction and, consequently, loyalty, ensuring sustained success in a competitive environment.